A Robust 6-lncRNA Prognostic Signature for Predicting the Prognosis of Patients With Colorectal Cancer Metastasis - Li, Shuyuan; Chen, Shuo; Wang, Boxue; Zhang, Lin; Su, Yinan; Zhang, Xipeng (Frontiers in Medicine, 2020)
Objective: Our study aimed to construct a robust long noncoding RNA (lncRNA) prognostic signature for colorectal cancer (CRC) metastasis. Methods: Differentially expressed lncRNAs were identified between metastatic CRC and non-metastatic CRC samples from The Cancer Genome Atlas Database (TCGA) using the edgeR package. The differentially expressed lncRNAs with prognosis of patients with CRC metastasis were identified by univariate Cox regression analysis, followed by a stepwise multivariate Cox regression model. The survminer package in R was used to identify the optimal cut-off point for high-risk and low-risk groups. The receiver operating characteristic (ROC) curves were plotted to assess this signature. To explore potential signaling pathways associated with these lncRNAs, Gene Set Enrichment Analysis (GSEA) analysis was performed. Results: A 6-lncRNA signature was built based on the lncRNA expression profile for CRC metastasis. The optimal cutoff value was used to classify high-risk and low-risk groups using the survminer package. The high-risk groups could have poorer survival time than low-risk groups. ROC curve result indicated that this lncRNA signature had the high sensitivity and accuracy. GSEA analysis results showed that the six lncRNAs were significantly enriched in several CRC metastasis-related signaling pathways such as “cell cycle”, “DNA replication”, “mismatch repair”, “oxidative phosphorylation”, “regulation of autophagy” and “insulin signaling pathway”. Conclusion: Our study constructed a 6-lncRNA model for predicting the survival outcomes of patients with CRC metastasis, which could become potential prognostic biomarkers and therapeutic targets for CRC metastasis.